Migration und ihre Determinanten im ost-westdeutschen Kontext nach der Wiedervereinigung: ein Literaturüberblick - Sascha Wolff (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2006)
A main feature characterising the transition process of Eastern Germany is the scope with which east-west migration took place before, during, and after the German unification. Overall, roughly 2.77 million East Germans left their territory to migrate to the west between 1989 and 2002 (gross migration). Taking into account west-east migration, cumulative net migration amounted to 1.3 million persons. These figures not only highlight the relevance of the migration phenomenon in the east-west German context. They also raise questions about the reasons and the determinants of this migration movement. Dealing with the influencing factors of emigration is particularly important against the backdrop of high expected east-west European migration movements in the course of and due to the eastern enlargement of the EU. Thus it is the objective of this paper to give an overview over the current state of economic research to migration in the east-west German context and in particular its determinants. The main studies within this area will be described and critically discussed.
Keywords: J61; J62; R23; 330; east-west German migration; determinations of migration